Teaching resistant learners in post-school education a guide to working with challenging behaviour - Lebor, Mervyn (Routledge, Taylor & Francis Group, 2023)
"This book explores various frameworks within which post-school education is situated and the practice that actually happens in classrooms and lecture-theatres, especially when things go wrong. Examining how and why some students choose to resist learning whilst undertaking tertiary education, this book provides practical tips and guidance for educators on how to work through difficult situations where learning isn't a student's priority. Considering both theory and practice, the book offers a range of practical solutions to difficult circumstances, such as the greater emphasis on distance learning; the growth of predatory or fake journals to the challenges of too much screen time; ghost writers and plagiarism; speaking out of turn, consistent lateness, absenteeism and even violent behaviour. Looking at contexts and behaviours where learning is rejected or ignored, through students' indifference or resistance, from a range of perspectives, this book is ideal reading for anyone working or involved in tertiary education, including teacher trainees, tutors, teacher educators, managers, administrators and lecturers working at universities and colleges, as well as students who may benefit from discussions of the problematic nature of learning"--